Analisis Manajemen Kepemimpinan Melalui Aplikasi Swot Pada Organisasi PSSI (Persatuan Sepakbola Seluruh Indonesia) - andri veno (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2016)
Just like an umbrella, PSSI, official Indonesian football organization have been changing to fulfill several organizational goals, and still undergoing some functions alongside regulation of FIFA and Indonesian law for the glorious and prestigious Indonesian football. In reorganizing PSSI, the government under The Ministry of Educations and Sports (Kemenpora) takes over PSSI’s role temporarily to rearrange management of the organization, and then the problems regarding to mafia and political issues inside of PSSI management can be resolved immediately. The management changes by the government is expected to become a turning point for the development of the future PSSI organization, so it can be reciprocal both with mission and vision of PSSI. The recent step from the government under Kemenpora in order to make all of the football perpetrators running their job is hold a tournament with competition system.